Actinomyces graevenitzii Pulmonary Abscess Mimicking Tuberculosis in a Healthy Young Man. Issue 6 (2014) - Gliga, Smaranda; Devaux, Mathilde; Woimant, Marine Gosset; Mompoint, Dominique; Perronne, Christian; Davido, Benjamin
Abstract : Pulmonary actinomycosis is a rare disease that is often misdiag-nosed as tuberculosis or lung cancer. Actinomyces graevenitzii is a relatively new recognized Actinomyces species isolated from various clinical samples. The authors report a case of pulmonary actinomycosis caused by A graevenitzii . A computed tomography examination revealed an excavated consolidation in the middle right lobe of a previously healthy young man who presented with a long history of moderate cough. Cultures of the bronchoalveolar lavage fluid confirmed the diagnosis of pulmonary abscess caused by A gravenitzii . At the three-month follow-up consultation and, after six weeks of high-dose amoxicillin, the pulmonary lesion had completely disappeared.